PENINGKATAN KESIAPSIAGAAN MASYARAKAT TERHADAP KEGAWATDARURATAN KESEHATAN RUMAH TANGGA MELALUI EDUKASI DAN SIMULASI - Ismi Nur Khasanah; Saumi Fijriyah; Budi Punjastuti; Dhiya Urrahman; Fahmi Baiquni (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2024)
Household health emergencies may occur suddenly and pose a serious threat to life if not managed promptly and appropriately. Limited community knowledge and preparedness often lead to delays in providing first aid before professional medical care is obtained. This activity aimed to improve community preparedness for household health emergencies through education and simulation. An educative–participatory approach with a pre-experimental one group pre-test and post-test design was applied. The intervention consisted of interactive health education, discussions, and first aid simulations for common household emergency conditions. Evaluation was conducted using questionnaires and observations before and after the activity and analyzed descriptively. The results demonstrated improvements in community knowledge, attitudes, and preparedness in recognizing and responding to household health emergencies. The combination of education and simulation proved effective in fostering responsive attitudes and increasing community confidence in emergency situations. This activity is expected to support promotive and preventive efforts in creating safer and more responsive household environments toward health emergencies.